A STUDY OF LOCAL WISDOM AS CULTURAL FOUNDATION IN TORAJA PROVERBS (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Toraja proverbs serve as a vital expression of local wisdom, encapsulating the cultural values, ethical principles, and social norms that shape the identity of the Tora ja people. This paper explores the cultural foundations embedded in Toraja proverbs. Through a qualitative analysis of proverbs, the study examines how these values influence interpersonal relationships, community dynamics, and ethical conduct within Toraja society. Findings reveal that proverbs not only guide individual behavior but also as guidance in a Toraja society. It includes the importance of familial bonds, cooperation, leadership, persistence, loyalty, fairness, wisdom, sincerity, humility, and diligence. These values reflect the essence of Toraja's cultural identity and provide timeless guidance for maintaining harmony and character development